Indonesian Governors’ Gender, Age, Education Level, Educational Background, Tenure and Their Tendency of Conducting Fraud - Sri Elviani; Ramadona Simbolon; Farida Khairani Lubis; Lusi Elviani Rangkuti; Ismail Nasution (Qubahan Academic Journal)
This study aims to determine the effect of governor characteristics on the occurrence of fraudulent activities in the Provincial Government in Indonesia. Gender, age, education level, education background and tenure are used as proxies for the demographic characteristics of governors. Data were collected from the Corruption Eradication Commission, the Supreme Audit Board and Indonesian Corruption Watch and analyzed using panel data regression. The results of this study indicate that the governors with accounting background are more likely not to be involved in fraud, while tenure has no effect on fraud. An interesting finding was obtained that education level and age have a negative effect on fraud. Fraud is higher when the governor is younger and has a lower level of education. This has implications for policy makers in Indonesia in preventing fraud by making regulations that take into account the demographic characteristics of candidates for governor in Indonesia. The results also show that the demographic characteristics of the Governor play an important role in preventing fraud.